2013
DOI: 10.1377/hlthaff.2012.1400
|View full text |Cite
|
Sign up to set email alerts
|

The Quality Of Care Delivered To Patients Within The Same Hospital Varies By Insurance Type

Abstract: In attempting to explain why hospitals vary in the quality of care delivered to patients, a considerable body of health policy research points to differences in hospital characteristics such as ownership, safetynet status, and geographic location as the most important contributing factors. This article examines the extent to which a patient's type or lack of insurance may also play a role in determining the quality of care received at any given hospital. We compared within-hospital quality, as measured by risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 29 publications
2
68
1
4
Order By: Relevance
“…Quanto ao ajuste de risco realizado, as variá-veis utilizadas neste estudo guardam similaridades com outros trabalhos 4,14,26,27,31 . Nos estudos nacionais, a idade, o sexo, a utilização de UTI, o tipo de admissão e o diagnóstico principal têm sido as principais variáveis usadas para a padronização de taxas e modelos de ajuste de risco, pois se encontram disponíveis nas bases brasileiras 28,29,33,34 .…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Quanto ao ajuste de risco realizado, as variá-veis utilizadas neste estudo guardam similaridades com outros trabalhos 4,14,26,27,31 . Nos estudos nacionais, a idade, o sexo, a utilização de UTI, o tipo de admissão e o diagnóstico principal têm sido as principais variáveis usadas para a padronização de taxas e modelos de ajuste de risco, pois se encontram disponíveis nas bases brasileiras 28,29,33,34 .…”
Section: Discussionunclassified
“…A maior proporção de hospitais públicos e de arranjo somente SUS classificados com desempenho pior que o esperado indica a ocorrên-cia de problemas que merecem ser investigados e monitorados. Entre os fatores que influenciariam as disparidades nos resultados de pacientes por fontes de pagamento de suas internações, estudos publicados por pesquisadores dos Estados Unidos discutem diferenças da prática clínica, acesso a tecnologias e procedimentos de alto custo e complexidade, além da indução ao uso de serviços desnecessários, impulsionados por mecanismos de mercado 26,40,41,42 . No entanto, vale ressaltar que limitações inerentes ao uso da mortalidade hospitalar global, bem como diferenças na gravidade do caso podem também explicar a variação aqui descrita.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Though not investigated here, factors such as the presence and quality of coverage, 36 frequency of language barriers, 37 and compliance with physician recommendations may vary according to socioeconomic status and may contribute to delay PAD recognition. 38 Studies have shown that patients who are uninsured, underinsured, or have Medicaid receive a lower quality of hospital care 36 and may have worse surgical outcomes and mortality. 39,40 Future studies are needed to understand the role socioeconomic factors play on both sides of the physician-patient interaction.…”
Section: Discussionmentioning
confidence: 99%